Anti Inflammatory Potential of Euphoria Hirta L. Leaves In Jaipur Region - Verma, Gunjan; Sharma, Vandana; Pareek, Ramesh (Asian Journal of Pharmaceutical Research and Development, 2021)
Introduction: Euphorbia hirta Linn. (E.hirta L.) is a medicinal herb belonging to the family Euphorbiaceae. It is commomly known as Asthma plant, Duddhi, Bara duddhi. It has been claimed for the various medicinal properties such as inflammation, diarrhoea, bronchitis, kidney stones, peptic ulcer, menstrual problems etc. Objective: the goal of our research work is to assessing the anti inflammatory activity of E.hirta L. leaves in regards to phytochemical studies. Methods: The method carragennan induced paw edema in rats was used to assess the anti inflammatory activity of aqueous extract of E.hirta L. leaves. The extract was obtained by maceration method and the analysis of phytochemicals was carried out by performing different chemical test in laboratory. Crude aqueous extract was given orally at different doses of 100mg/kg, 300mg/kg and 500mg/kg in wistar albino rats 30mins before carragennan injection. Ibuprofen (50mg/kg) was taken as reference drug. The volume of paw edema was measured by using plethysmometer at 1, 2 and 3 hr after carragennan administration. Results: The preliminary phytochemical study reveals the availibility of flavonoids, terpenoids, sterols, glycosides, tannins etc in different solvents of crude drug extract. The anti inflammatory effect of crude drug extract was exhibited a remarkable dose dependent reduction in paw edema volume. The inhibitory effect was highest at 500mg/kg dose of drug. Extract and ibuprofen showed 52% and 66% inhibition of paw edema respectively, at 3hr after carragennan administration. Conclusion: E.hirta L. leaves aqueous extract has a strong anti inflammatory activity. These consequences help in the traditional uses of the plants and in the development of new treatments.